Communications Research in Action : Scholar-Activist Collaborations for a Democratic Public Sphere - Aslama, Minna; Napoli, Philip M. (Donald McGannon Communication Research Center's Everett C. Parker book series., 2011)
Essays spanning topics such as the effect of ownership concentration on children's television programming, the media's impact on community building, and the global consequences of communications research will not only be valuable to scholars, activists, and media policymakers but will also be instrumental in serving as a template for further exploration in collaboration. --Book Jacket.